Web-based pollution monitoring system for the Lake Ohrid - Mitreski, Kosta; Davchev, Dancho; Koneski, Z (WIT Press, 2000)
In this paper, we will present a Web-based pollution monitoring system for Lake Ohrid. Our intention is to describe some of the processes that contribute to the eutrophication of Lake Ohrid. Our work is related to the ecological state of Lake Ohrid. Tectonic by origin, Lake Ohrid is situated in the southwestern part of the Republic of Macedonia. The size of the lake is 358 square kilometres. Its average depth is 151m and the maximum depth is 289m. "Man-made" eutrophication, in the absence of control measures, proceeds much faster than the natural phenomenon and is the major reason for pollution of this lake. A Dynamic Integrated Monitoring System (DIMS) was previously presented in another paper. The monitoring system is based on on-line measurements. One of the main objectives of DIMS is to provide a real-time monitoring and efficient protection of the environment. In this paper, we present a Web-application for handling the data for the pollution monitoring system. Data acquisition and analysis is performed by a DBMS server and then presented in HTML format in regular predefined time intervals. The Web server and corresponding software are used for this presentation. In this way the data and its analysis is performed in one place and they are available to any user having only a web browser. The Web-based pollution monitoring system is implemented using UNIX/RDBMS environment and GIS software.